Disrupted downstream migration behaviour of European silver eels (Anguilla anguilla, L.) in an obstructed river - Besson, Marc L.; Trancart, Thomas; Acou, Anthony; Charrier, Fabien; Mazel, Virgile; Legault, Antoine; Feunteun, Eric (Environmental Biology of Fishes, 2016)
International audience In the European eel (Anguilla anguilla, L.), the steep decline of reproductive silver eels is partly due to disorientation and mortality during their downstream migration, when facing turbines, but also reservoirs and dams. In the Frémur, an obstructed river in Brittany, which is representative of the western coastal hydrosystem of France, five hydrophones were used to study the downstream migration patterns of twenty acoustically-tagged silver eels. Using this acoustic telemetry design, we showed that, despite exceptionally favourable environmental conditions, silver eels experienced important issues to move downstream the river. Indeed, 75 % of eels were delayed and up to 65 % were definitively stopped in their downstream migration. The 14 m high Bois-Joli dam, located at 5 km from the estuary, and its reservoir were the major obstacles to downstream movements. Eels that managed to move downstream only passed over the dam crest, during the night, and under highly favourable environmental conditions: river flow >1.2 m3.s−1 and water level at the dam >28.26 mNGF (Niveau Général de la France; baseline mean sea level for France). Three different downstream migration behaviours were observed: “successful migrants”, “uncertain migrants” and “unsuccessful migrants”. None of them were related to biological traits, suggesting a behavioural plasticity of silver eels. This study provides useful information to manage eel populations in such water basins that are very likely to be applied to all water reservoirs and dams, which are widespread through the distribution range of European eels.